Computer-aided design and diagnosis methods for biomedical applications - Bajaj, Varun; Sinha, G. R., 1975- (Boca Raton : CRC Press, 2021)
"The Computer-aided design (CAD) plays key role to improve biomedical system for various applications and helps in detection, identification, predication, analysis and classification of diseases, management of chronic condition, and delivery of health services. Present book discusses uses of CAD to solve real world problems and challenges in Biomedical systems with the help of appropriate case studies and research simulation results. Aiming to overcome the gap between CAD and biomedical science intricacies, it explains behaviours, concepts, fundamentals, principles, case studies and future research directions including automatic identification of related disorders using CAD. Features: Proposes CAD for study of biomedical signals for understanding physiology and to improve healthcare system for diagnosis and identification of health disorders Presents concepts of CAD for biomedical modalities for different disorders Discusses design and simulation examples, issues and challenges Illustrates bio-potential signals and their appropriate analysis for studying different disorders Includes case studies, real-time examples and research directions This volume is aimed at researchers, graduate students in biomedical engineering, image processing, biomedical technology, medical imaging and health informatics"--
Includes index.
OCLC-licensed vendor bibliographic record.
Keywords: Biomedical materials; Computer-aided design; Biomedical engineering; MEDICAL / Biotechnology; SCIENCE / Physics